Comparação de técnicas de desinfecção do tubo de entrada de medicamento da bolsa de diálise peritoneal - Conti, Adriana (2017)
Introduction: Peritonitis remains a major complication in peritoneal dialysis patients, with the predominant infectious agent being coagulase-negative Staphylococcus (CNS). Intraperitoneal administration of antibiotics is the required treatment, however, no consensus exists on the appropriate disinfection of the medication port (MP). Objective: To compare different disinfection techniques for the peritoneal dialysis bag MP. Methods: An experimental study was conducted testing different cleaning agents (70% alcohol vs 2% chlorhexidine) and time periods (5, 10 and 60seconds) for disinfection of the MP. Four microorganisms (S. aureus, E.coli, A. baumannii and C.parapsilosis) were prepared for use as contaminants of the MP. MP were incubated in Tryptic soybroth at 36ºC for 24 h, after which, they were seeded on a Biomérieux® blood agar plate and incubated for 24 h at 36ºC. Results: A total of 240 PD bags were contaminated with four different microorganisms. Two positive cultures (E. coli and S. aureus) were identified, both after disinfection with alcohol after 5 and 10 seconds of friction, and none in the chlorhexidine group. Conclusion: although there was no statistical difference between the antiseptics used and the cleaning time, the use of chlorhexidine for 1 minute was the only one in which there was no bacterial growth, therefore we considered this recommendation.